Cover Feature: Dissipative Dynamic Libraries (DDLs) and Dissipative Dynamic Combinatorial Chemistry (DDCC) (ChemSystemsChem 6/2022). Issue 6 (17th October 2022) - Del Giudice, Daniele; Spatola, Emanuele; Valentini, Matteo; Ercolani, Gianfranco; Di Stefano, Stefano
Abstract : The Cover Feature shows puzzle pieces that initially change their shape, and consequently their interconnection, to eventually go back to their initial state, resembling the behavior of the components in a dissipative dynamic combinatorial library. Design by Daniele Del Giudice. More information can be found in the Concept by Gianfranco Ercolani, Stefano Di Stefano and co‐workers .